Anticytomegaloviral activity of methotrexate associated with preferential accumulation of drug by cytomegalovirus-infected cells. - Wachsman, M (1996)
We extend the observation that inhibitors of pyrimidine biosynthesis are active against human cytomegalovirus by demonstrating that methotrexate (MTX) has preferential activity against cytomegalovirus replication. The 50% and 90% inhibitory concentrations of MTX for inhibition of cytomegaloviral DNA replication at 3 days postinfection in MRC-5 cells were 0.05 and 0.2 microM, respectively. No cell toxicity was observed in uninfected confluent cells at the highest concentration tested (1 microM). Under similar conditions (3 days of treatment with 0.2 microM MTX), intracellular dTTP pools were diminished in cytomegalovirus-infected cells (87% decrease relative to untreated infected cells, P < 0.001) but were not reduced in uninfected cells. A potential explanation for the preferential antiviral effect of MTX was that human cytomegalovirus-infected cells preferentially accumulated MTX. Increased intracellular accumulation and increased polyglutamation of MTX were observed in cytomegalovirus-infected cells compared with uninfected cells. Increased uptake of [3H]MTX by cytomegalovirus-infected cells was first observed at 48 h postinfection, with threefold-higher accumulation within infected cells. By 96 h, accumulation had increased to approximately fourfold in comparison with uninfected cells. The uptake of [3H]MTX was saturable and was blocked by addition of unlabelled MTX. Intracellular MTX in infected cells was almost entirely in the polyglutamated form, as demonstrated by thin-layer chromatography, whereas intracellular MTX was almost exclusively in the parent form in uninfected cells.